2022
DOI: 10.1017/pds.2022.80
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Creating Solution Concepts Based on the Use of References

Abstract: The use of already validated systems as references for the development of solution concepts offers the potential to increase process efficiency. It is important to understand how the use of references impacts the development of solution concepts. Therefore, the representation of solution concepts in an engineering project of two student cohorts are analyzed and compared. The first cohort is provided with few and the second cohort with extensive references. The results of the study show that the increased use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…C.9 -Use of references in concept development: Schlegel et al (2022) show the implication of references for a system's maturity in the early phase. However, less than 30% of the publications analysed consider the use of references at all.…”
Section: C6 -Degree Of Maturity Of a Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…C.9 -Use of references in concept development: Schlegel et al (2022) show the implication of references for a system's maturity in the early phase. However, less than 30% of the publications analysed consider the use of references at all.…”
Section: C6 -Degree Of Maturity Of a Conceptmentioning
confidence: 99%
“…A study in a student engineering project showed that through using references for the development of concepts, the level of embodiment information was increased, and a higher amount of already validated subsystems and a more detailed and critical functional understanding was achieved. (Schlegel et al, 2022). Existing definitions of the term concept do not yet comprehensively address the aspect of incorporating references.…”
Section: Introductionmentioning
confidence: 99%